Cancer Gene Profiling Methods and Protocols - Grützmann, Robert; Pilarsky, Christian (Humana Press, 2010)
Over the last few years, the methods for analyzing cancer-related genes on a molecular level have changed rapidly. The advent of incredible new technology, such as automated sequencing, has served as a catalyst for many advances in the area of gene profiling, and has enabled the research community to investigate populations of cells in a given tissue. Cancer Gene Profiling: Methods and Protocols examines the world of cancer gene profiling in light of these new advances, providing highly developed microarray techniques alongside modern methods for arraying tissues and proteomics. Chapters bring together the experiences of leading scientists in each method of profiling, providing a clear overview of the ground-breaking techniques used to perform these experiments effectively. Composed in the highly successful Methods in Molecular Biology™ series format, each chapter contains a brief introduction, step-by-step methods, a list of necessary materials, and a Notes section which shares tips on troubleshooting and avoiding known pitfalls. Comprehensive and state-of-the-art, Cancer Gene Profiling: Methods and Protocols is a fundamental guidebook for researchers in the field of cancer gene profiling, as well as for those individuals in the area of biomedical/translational research
Keywords: Medicine & Public Health; Oncology; Cancer Research; Gene Expression; Medicine; Cancer research; Gene expression; Aufsatzsammlung